A New Arab Urban: Gulf Cities of Wealth, Ambition, and Distress - Burak, Erdim (Histories of Postwar Architecture, 2021)
In this volume, editors Harvey Molotch and Davide Ponzini take a decidedly different approach to the analysis of Gulf cities to show that what is happening in the United Arab Emirates and Qatar is not so abnormal and is more indicative of emerging trends in urbanization than what first meets the eye. Organized under four thematic sections, the volume brings together a wide-array of essays, generated by a diverse group of scholars from a numerous disciplines including architecture, architectural history, urban planning, area studies, political science, sociology, geography, and art. Taking cues from Robert Venturi, Denise Scott Brown, and Steven Izenour’s well-known book, Learning from Las Vegas (1972), this volume situates Gulf cities within the transnational contexts of colonialism, globalization, neo-liberalism, and emergent trends of human and capital migration.